Strategi Komunikasi Pemasaran Media Konvensional Balikpapan TV di Era Konvergensi Media - Fahruraji Muhammad (Faculty of Ushuluddin and Dakwah, UIN K.H. Abdurrahman Wahid Pekalongan, Central Java, Indonesia, 2023)
The purpose of this study is to find out the development of Balikpapan TV Marketing Communication Studies in the Media Convergence Era. This research is conducted at the Balikpapan Television Office using descriptive qualitative analysis methods. The focus of the research is to formulate Balikpapan TV's marketing communication strategy so that it is able to compete in the media convergence era by using the marketing mix strategy. The data collection technique used purposive sampling and produces primary and secondary data sources. Data analysis techniques used descriptive qualitative data analysis, including data collection, data reduction, data presentation and drawing conclusions. The results of the research include Balikpapan TV's advertising activities by advertising in conventional mass media, Balikpapan TV's promotional activities by providing special offer packages to potential customers, Balikpapan TV's event activities and experiences by utilizing its Event Organizer services, Balikpapan's public relations and publicity activities. TV focuses more on efforts to establish cooperation in order to gain consumers and increase revenue turnover, Balikpapan TV's direct and interactive selling activities by utilizing its social media, and Balikpapan TV's personal selling activities by dividing people in the marketing team to make direct sales to candidates consumer.